Sosialisasi Pembuatan Media Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Kualitas Pembelajaran Guru SD Negeri 057761 Kwala Gebang - Rusli Rusli; Patri Janson Silaban; Lasma Silaban (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Preparing a golden generation for the future that can compete in the progress of the times can be done through good education. So that education is a forum for students to be able to develop all the skills they have. As time progresses, technological progress also develops. The rapid development of technology also has an impact on the world of education. Learning activities cannot be separated from methods, models, teaching aids and also media. Teachers can use learning media as a means of conveying knowledge to their students.